Regulation of pharmaceuticals in developing countries : legal issues and approaches - Jayasuriya, D.C. (WHO GenevaCH, 1985)
Considers source of the constitutional, administrative and legal principles and technical considerations applicable to health legislation and in particular to drug legislation in developing countries. Discusses possible approaches to formulating and effecting a legal framework on pharmaceuticals identifying different legislative models and structures previously devised. Specific aspects focussed on include importation, manufacture, exportation, sale, and distribution of pharmaceuticals, drug quality and safety and control of information on pharmaceuticals eg. labelling and advertising.